2019
DOI: 10.1021/acsbiomaterials.8b01308
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Templating of Extrinsic Freeze-Casting for Macro–Microporous Biomaterials

Abstract: As with most biological materials, natural bone has hierarchical structure. The microstructural features of compact bone are of various length scales with its porosity consisting of larger osteons (∼100 μm diameter) and vascular channels, as well as smaller lacuna spaces (∼10 μm diameter). In this study, the freeze-casting process, which has been previously used to form biocompatible porous scaffolds (made with hydroxyapatite, HA) has been improved to mimic the intrinsic hierarchical structure of natural bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 44 publications
(73 reference statements)
0
25
0
Order By: Relevance
“…As mentioned earlier, achieving biomaterials whose morphology is inspired by bone's ultrastructure can be attempted using ice templating. Hap, 37,94,[103][104][105][106][107] one of the main components of bone, is consequently holding a dominant place in the fabrication of scaffolds for bone tissue engineering applications. Hap scaffolds were obtained through the use of electric field assisted ice templating.…”
Section: Scaffold Composition -How To Define the Composition Of Ice Templated Scaffolds For 3d Cell Culture?mentioning
confidence: 99%
“…As mentioned earlier, achieving biomaterials whose morphology is inspired by bone's ultrastructure can be attempted using ice templating. Hap, 37,94,[103][104][105][106][107] one of the main components of bone, is consequently holding a dominant place in the fabrication of scaffolds for bone tissue engineering applications. Hap scaffolds were obtained through the use of electric field assisted ice templating.…”
Section: Scaffold Composition -How To Define the Composition Of Ice Templated Scaffolds For 3d Cell Culture?mentioning
confidence: 99%
“…Recent research has also demonstrated the incorporation of three-dimensional (3D) printing sacrificial scaffolding in freeze-cast monoliths to yield macrostructural control. 31 This shows promise for future applications that look to have substantial control over several length scales. By combining the advents of structural control from the macro-to the microscale in the field of freeze casting, with the structural diversity of diatom frustules, and further nanostructural functionalizations (i.e., metal−organic frameworks, zeolites, nanoparticles, and shape-preserving chemical alterations), the future of diatomite freeze-cast monoliths will potentially produce a wide-reaching array of applications.…”
Section: T H Imentioning
confidence: 99%
“…The resulting hierarchical structure of functional materials with the controlled compositions is expected to improve the electrochemical performances owing to the abundant surface‐exposed active sites, the rapid charge transfer, the fast 3D electron/ion/mass transporting pathways, the large accessible areas, the open spaces for the redox sites, and the ability to form structures with free volumes which provides stress buffering during electrochemical reaction. [ 75–84,86,87 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the types of functional materials include ceramic, [75,76] metal, [33][34][35]38] polymer, [77][78][79] carbon, [36,80,81] and even biological materials. [82][83][84] Another advantage is that various alterations to processing conditions lead to drastic changes and controls in the micro and macrostructures of as-obtained ice templated scaffolds. The resulting hierarchical structure of functional materials with the controlled compositions is expected to improve the electrochemical performances owing to the abundant surface-exposed active sites, the rapid charge transfer, the fast 3D electron/ion/mass transporting pathways, the large accessible areas, the open spaces for the redox sites, and the ability to form structures with free volumes which provides stress buffering during electrochemical reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation